Penerapan Model Machine Learning Algoritma Gradient Boosting dan Linear Regression Melakukan Prediksi Harga Kendaraan Bekas - Leriansyah Putra Nasyuli; Imran Lubis; Andi Marwan Elhanafi (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The increase in the number of new car releases coupled with the increasingly massive advertisements about the latest cars in the city of Medan, makes consumers or the public more interested and encouraged to be able to exchange (sell) their cars and replace them with the latest cars, so this creates used cars that are still suitable for use to be re-sold and bought to other consumers so that it makes the marketing of used cars very large. This is proven by the large number of requests for used car purchases in the city of Medan to meet their needs for four-wheeled vehicles. Used vehicles, especially 4-wheeled vehicles, have varying prices and are always different from one seller to another, which causes confusion for buyers about used car prices. To overcome this problem, the authors use data mining techniques to predict used vehicles, especially 4-wheeled vehicles. The results applied are make predictions using the gradient boosting algorithm and the linear regression algorithm which produces used car predictions.